POLA ADAPTASI MANUSIA TERHADAP LINGKUNGANNYA - Sambung Widodo (Berkala Arkeologi, 2005)
Since prehistoric times, human adaptation patterns to their environment have manifested certain patterns that are closely related to human subsistence strategies in adapting to their natural environment. The choice of location for human habitation is strongly influenced by efforts to minimize the use of energy and time in exploiting and distributing sources of subsistence. There is a tolerance between the location of the site and the pattern of human adaptation to its natural environment. Factors related to environmental conditions are very important in choosing a location, in addition to other factors apart from economic and political factors.